1996
DOI: 10.1063/1.115661
|View full text |Cite
|
Sign up to set email alerts
|

Al/Al2O3/Al single electron transistors operable up to 30 K utilizing anodization controlled miniaturization enhancement

Abstract: We have developed a method, anodization controlled miniaturization enhancement (ACME), to make ultrasmall tunnel junctions. Anodization of electron-beam fabricated Al/Al2O3/Al tunnel junctions reduces their effective areas and capacitances, which realizes single electron transistors operating at high temperatures up to nearly 30 K. The limit of the increase in the charging energy is attributed to the initial scattering in the junction sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…The difference in the two values presumably arises because of variations in tip geometry which affect the local electric field. These values of −dt/dV are slightly higher than values measured for conventional anodization of Al films but are consistent with values recently reported in the literature for nonplanar geometry [12].…”
Section: Fabrication Proceduressupporting
confidence: 92%
See 1 more Smart Citation
“…The difference in the two values presumably arises because of variations in tip geometry which affect the local electric field. These values of −dt/dV are slightly higher than values measured for conventional anodization of Al films but are consistent with values recently reported in the literature for nonplanar geometry [12].…”
Section: Fabrication Proceduressupporting
confidence: 92%
“…Nakamura et al have shown that gross anodization of an entire Al/Al 2 O 3 SET device, guided by in situ electrical measurements, can be used to shrink its dimensions and consequently raise its operating temperature [12]. The limitation in this approach is the inevitable asymmetrical size of the tunnel junctions which are fabricated by electron-beam lithography.…”
Section: Discussionmentioning
confidence: 97%
“…With values from Fig. 4 [24][25][26][27] Our value for specific capacitance is therefore in line with previously measured values for standard Al-AlO x -Al junctions.…”
Section: Low Temperature Propertiessupporting
confidence: 74%
“…In this figure the condition for The upper shadowed region is excluded by the stability condition. The other shadowed regions are excluded by the experiments MACRO [17], KEK [19], MICA [15] and CDMS [16]. We take q = 1 for simplicity (see text).…”
Section: Cosmological or Observational Constraints On Region Of Pamentioning
confidence: 99%